The law school experience: Adopting regulation strategies - Macaraan, Maryrose C. (Animo Repository, 2021)
Law school is the training ground for all future lawyers. While the law profession can be a compelling career opportunity, developing the necessary skills required for the profession can be a tough journey, and can be overwhelming. Experience of psychological distress among law students is evident in various research studies. The aim of this paper is to explore the literature on regulation strategies that would help law students survive the rigors of law school focusing on both academic and emotional regulation approaches. Self-regulated learning promotes and sustains behaviors that help an individual maintain motivation to achieve goals. Regulating emotions enables a person to manage emotional experiences effectively. The capacity to regulate learning and emotions are essential skills for law students to help them survive the rigors of law school.